Maxillofacial Plastic and Reconstructive Surgery - Kim, Seong-Gon
Maxillofacial Plastic and Reconstructive Surgery is an open access, peer-reviewed journal that publishes clinical and basic research on the epidemiology, etiology, treatment, and prevention of congenital and acquired anomalies/defects involving the oral and maxillofacial regions. The journal focuses on investigating the causative factors of oral and maxillofacial anomalies/defects and the development of surgical methods and materials for morphological reconstruction or functional restoration. Maxillofacial Plastic and Reconstructive Surgery is the official journal of the Korean Association of Maxillofacial Plastic and Reconstructive Surgeons. The journal welcomes high quality original articles, case/technical reports, collective or current reviews, editorials, and brief communications and covers the following main subjects: • Congenital deformity of maxillofacial area • Dental and maxillofacial reconstruction • Tissue engineering related to maxillofacial reconstruction • Cosmetic surgery and related material research of maxillofacial area • Orthognathic surgery-related research • Temporomandibular joint reconstruction • Anatomic research of maxillofacial area.